2018
DOI: 10.1111/aos.13993
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival melanoma and electrochemotherapy: preliminary results using 2D and 3D cell culture models in vitro

Abstract: Purpose To investigate the cytotoxic effect of bleomycin, mitomycin C ( MMC ) and Fluorouracil (5‐ FU ) in combination with electroporation ( EP ) on human conjunctival melanoma ( CM ) and normal conjunctival cell lines using 2D and 3D cell culture systems in vitro . Methods Two CM ( CRMM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
(72 reference statements)
0
23
0
1
Order By: Relevance
“…39 Methods used to increase drug penetrance into spheroids have also been described, including electrochemotherapy. 40 With respect to drug efficacy, studies have shown that in 2D cell culture systems potency is enhanced when compared with 3D models, 21 such that the predicted clinical efficacy in patients is often overestimated. 1 Interestingly, in our study, doxorubicin had similar effects on 92.1 and MM66 cells grown in 2D or 3D culture irrespective of spheroid parameters such as compactness, growth rate, or cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…39 Methods used to increase drug penetrance into spheroids have also been described, including electrochemotherapy. 40 With respect to drug efficacy, studies have shown that in 2D cell culture systems potency is enhanced when compared with 3D models, 21 such that the predicted clinical efficacy in patients is often overestimated. 1 Interestingly, in our study, doxorubicin had similar effects on 92.1 and MM66 cells grown in 2D or 3D culture irrespective of spheroid parameters such as compactness, growth rate, or cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for difference in response are multifaceted and include physical features pertinent to electrochemotherapy, such as unavailability of the drug and insufficient coverage with electric field and biological, pertinent to patient, such as previous treatments, difference in tumor microenvironment, mutational status, and so on. 2,14,18 Thus, electrochemotherapy is still evaluated in different types of cancer, either in vitro or in vivo, including colon carcinoma CT26 (in vitro) 19 ; bladder cancer SW780 (in vitro and in vivo) 20 ; fibroblasts, human umbilical vein endothelial cells (HUVEC; in vitro) and two squamous cell carcinomas, CAL-27 and SCC-4 (in vitro) 21 ; ovarian cell lines OvBH-1 and SKOV-3 (in vitro) 22 ; human neuroblastoma SH-SY5Y cells (in vitro) 23 ; BRAF-mutated melanoma cells (SK-MEL-28) and their counterpart without mutation, CHL-1 cells (in vitro) 24 ; chemoresistant uveal melanoma cells (Mel 270, 92-1, OMM-1, OMM-2) (in vitro) 25 ; primary cells from metastatic pancreatic tumors (in vitro) 26 ; human papillomavirus (HPV)-positive head and neck squamous cell carcinoma 2A3 (in vitro and in vivo) 27 ; Lewis lung carcinoma and CT 25 colorectal carcinoma (in vivo) 28 ; conjunctival melanoma CRMM1 and CRMM2 and normal conjunctival epithelial cells HCjE-Gi (in vitro) 29 ; radioresistant head and neck squamous cell carcinoma Fa-DuRR (in vitro and in vivo) 30 ; and small cell lung cancer H69AR cells (in vitro). 31 In general, it was demonstrated that electrochemotherapy with bleomycin or cisplatin causes immunogenic cell death in colon carcinoma 19,28 ; that human endothelial cells are more susceptible to electrochemotherapy than tumor cells, 21 supporting the antivascular effect in vivo; that electrochemotherapy is effective in ovarian carcinoma cells resistant to standard therapy 22 ; and that electrochemotherapy is also effective in neuroblastoma and primary pancreatic tumor cells, which was not demonstrated before.…”
Section: Electrochemotherapy: New Tumor Entities and New Combinationsmentioning
confidence: 99%
“…An image analysis and the integrated algorithms offer a quantitative characterization and a more precise calculation of various morphological features of the tested spheroids. Moreover, an image analysis complements the established assays for the spheroid monitoring, while it provides a comprehensive platform with a variety of techniques, such as statistical analysis, graph representation and computational topology and, therefore, 3D visualization [ 17 ]. In previous studies of our group, various EP parameters and differing concentrations of 5-FU, Mitomycin C and bleomycin were tested to identify the structural changes of the spheroids histologically and chemically, and to assess the toxicity of the tested drugs on conjunctival 2D and 3D cell models [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an image analysis complements the established assays for the spheroid monitoring, while it provides a comprehensive platform with a variety of techniques, such as statistical analysis, graph representation and computational topology and, therefore, 3D visualization [ 17 ]. In previous studies of our group, various EP parameters and differing concentrations of 5-FU, Mitomycin C and bleomycin were tested to identify the structural changes of the spheroids histologically and chemically, and to assess the toxicity of the tested drugs on conjunctival 2D and 3D cell models [ 17 ]. The CRMM1 cell lines were most sensitive to 5-FU and the CRMM2 cell lines to MMC but the cytotoxic effect of the drugs was not further enhanced by EP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation